beta-1 Integrins mediate tumour cell adhesion to quiescent endothelial cells in vitro - Price, E A; Coombe, D R; Murray, J C (British journal of cancer, 1996)
Metastatic spread of some solid tumours is thought to depend upon the adhesion of tumour cells to the vascular endothelium followed by extravasation into surrounding tissues. We investigated the role of beta 1 integrins in the adhesion of the breast adenocarcinoma cell line MDA-MB-231 and the melanoma cell line RPMI-7951 to quiescent human umbilical vein endothelial cells (HUVEC) in vitro. In the course of adhesion assays, tumour cells were observed to adhere to quiescent HUVEC monolayers, particularly at endothelial cell-cell junctions. Immunohistochemistry revealed concentration of beta 1 integrin expression at these sites. Adhesion was reduced by pretreatment of either tumour cells or HUVEC with antibodies against beta 1 integrins. Simultaneous treatment of HUVECs and tumour cells with these antibodies produced an additive blocking effect, consistent with a heterotypic adhesion mechanism. Our data suggest that tumour cell and endothelial beta 1 integrins may play a crucial role in the arrest and migration of tumour cells through the vascular endothelium in the absence of endothelial 'activation'.